Taxation and accounting expertise of MYPES in the money laundering process 2018-2019 - Prado-Ramos, Ronald (2022)
Objective: To demonstrate the influence of taxation on the accounting expertise of micro and small entrepreneurs in a process of money laundering. Method: The study was quantitative, descriptive and exploratory; the non-experimental transectional study. A field inspection was carried out, with observations of the micro and small entities using surveys during the 2018-2019 period. Results: Taxation directly influences the accounting expertise practiced by MYPES since the expert practice is determined from an accounting purely for tax purposes, with the formulation of external professionals that contains inconsistencies and inaccuracies with the transactions carried out by their organization. Conclusions: The Data obtained as a result of the study have made it possible to establish that micro and small companies are at the mercy of a Taxation that conditions their accounting and therefore the accounting expertise practiced, weakening it, to be dismissed by the judge.